Dynamics Analysis of a Single Leg of Quadruped Robots Based on Udwadia-Kalaba Theory - Liang Bin; Yuan Liang; Ran Teng; Xiao Wendong; He Li (Jixie chuandong)
Traditionally, the Lagrangian method is used to deal with the dynamics of multi-body systems. However, in the solution process, Lagrangian multipliers are introduced, which increases the difficulty of solving the explicit dynamics equations. To address the complex problem of modeling the dynamics of a quadruped robot, a single-legged model of quadruped robots based on Udwadia-Kalaba (UK) theory is investigated and a new method for solving its explicit dynamics equations is established. To simplify the process of obtaining the equations, the UK equation is used to deal with the motion constraints. Considering the uncertainty of the realistic environment, a nonlinear controller is designed to track the motion trajectory using the principle of sliding mode control. The results of numerical simulations prove the correctness and effectiveness of the dynamics equations and the controller.